EVALUASI FAKTOR TROUBLE ALAT YANG MEMPENGARUHI PRODUKTIVITAS BONGKAR MUAT DI DERMAGA INTERNASIONAL PT PELINDO MULTI TERMINAL JAMRUD - Setiawan, Yuda; Rahmawati, Maulidiah; Ratnaningsih, Dyah; Nugraha, Bugi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2025)
Loading and Unloading Productivity is a value that states how resources should be managed and used in order to achieve something optimally. The occurrence of equipment problems that hamper the loading and unloading work, the equipment provider carries out more maintenance on the loading and unloading equipment to avoid a decrease in loading and unloading productivity at the port. The research methods used by researchers are descriptive statistical research methods and Fishbone Analysis. Based on the research results, it can be concluded that the occurrence of loading and unloading equipment trouble factors that affect loading and unloading productivity is a combination of method factors (inadequate schedule), materials (excessive use of equipment without a time lag), humans (lack of mechanical attention to the planned maintenance system). , and maintenance (lack of preventive maintenance and carried out only during trouble) which is not optimal is the main cause of problems with loading and unloading equipment and results in a decrease in loading and unloading productivity.